Erratum: WEN-LI MA & LI-ZHEN LI (2012) A new species of Lesteva Latreille (Coleoptera, Staphylinidae, Omaliinae) from Zhejiang, East China. Zootaxa, 3530, 74–76. - Ma, Wen-Li; Li, Li-Zhen (Zootaxa, 2012)
(Erratum)